Clinical impact of structured follow-up after pancreatic surgery - Tjaden, Christin; Michalski, Christoph; Strobel, Oliver; Giese, Nathalia; Hennche, Anne-Kathrin; Büchler, Markus W.; Hackert, Thilo (Pancreas, 2016)
ObjectivesStructured follow-up after surgery for pancreatic ductal adenocarcinoma (PDAC) remains controversial and is currently not recommended due to a supposed lack of therapeutic consequences. Furthermore, it is not clear whether noncancer patients after pancreas resection need to be seen in the